Analysis of Using Film Subtitles to Improve Students’ Speaking Ability at SMPN 21 Makassar - Gandhy, Dwi Shintia; Atmowardoyo, Haryanto; Muhayyang, Maemuna (Journal of Excellence in English Language Education, 2024)
Speaking is a productive skill in which the activity involves two or more people interacting to transfer or get messages and information. The objectives of this study are to find out if the use of film subtitles is effective for improving students' speaking ability. The researcher employed a one-group pre- and post-test experimental design utilizing quantitative methods. Data collection was conducted through pre-tests, treatments, post-tests, and questionnaires. The results showed that there was a significant relationship between students' English-speaking ability before watching movies with subtitles and after watching movies without subtitles. This means that watching movies with subtitles can improve students' speaking ability at SMPN 21 Makassar.